Functionalization and characterization of cotton with phase change materials and thyme oil encapsulated in beta-cyclodextrins - Scacchetti F.A.P. (2017)
The aim of this work was to study the production of comfortable cotton plain-weave fabrics with antibacterial and antifungal characteristics through a simple finishing process, which consists in applying microcapsules of phase change materials (mPCM), monochlorotriazinyl-β-cyclodextrin (MCT-β-CD) and thyme oil. The fabrics were characterized by Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Contact Angle and Infrared Thermography. The thyme oil release was also analyzed, as well as the antibacterial and antifungal activity. The materials treated with 20 μL/mL of thyme oil have shown anomalous oil release mechanisms, according to the Korsmeyer-Peppas model, and activity against Staphylococcus aureus, Escherichia coli, Trichophyton rubrum, Pseudomonas aeruginosa and Candida albicans. Therefore, it was reached the conclusion that mPCM, conjugated with thyme oil encapsulated in MCT-β-CD, proved to be an interesting option to produce materials possessing thermoregulation properties with putative clinical relevance for the prevention of infections, particularly dermatophytosis. © 2017 Elsevier